Communication Strategies: What Indonesian EFL Learners Do in Casual Conversation? - Fadhila Yonata; Dewi Amalia Saptani (Institut Agama Islam Negeri Palopo, 2019)
In tackling casual conversation, most foreign language learners have problems in negotiating the intended meaning smoothly. One of the reasons is the lack of optimization of communication strategies to compensate communication breakdowns. This study attempts to reveal Indonesian advance English learners actual competence in engaging in a casual conversation. The data were taken from two recorded conversations lasted for 15 minutes which were then transcribed and analyzed with respect to communication strategies by implementing spoken discourse analysis. The percentage of kind of communication strategies results suggest that filler is the most frequent strategy used by speakers, followed by repetition, appeal for help and self-repair. These findings show that the participants have enough linguistic resources but having problem in verbalizing their mental concept due to insufficient practice.